Genes for Yield Stability in Tomatoes - Josef Fisher; Dani Zamir (Advanced Genetics, 2021)
Abstract Breeding plant varieties with adaptation to unstable environments requires some knowledge about the genetic control of yield stability. To further this goal, a meta‐analysis of 12 years of field harvest data of 76 Solanum pennellii introgression lines (ILs) is conducted. Five quantitative trait loci (QTL) affecting yield stability are mapped; IL10‐2‐2 is unique as this introgression improved yield stability without affecting mean yield both in the historic data and in four years of field validations. Another dimension of the stability question is which genes when perturbed affect yield stability. For this the authors tested in the field 48 morphological mutants and found one ‘canalization’ mutant (canal‐1) with a consistent effect of reducing the stability of a bouquet of traits including leaf variegation, plant size and yield. canal‐1 mapped to a DNAJ chaperone gene (Solyc01g108200) whose homologues in C. elegans regulate phenotypic canalization. Additional alleles of canal‐1 are generated using CRISPR/CAS9 and the resulting seedlings have uniform variegation suggesting that only specific changes in canal‐1 can lead to unstable variegation and yield instability. The identification of IL10‐2‐2 demonstrates the value of historical phenotypic data for discovering genes for stability. It is also shown that a green‐fruited wild species is a source of QTL to improve tomato yield stability.